2022
DOI: 10.3389/fmars.2022.1004096
|View full text |Cite
|
Sign up to set email alerts
|

Grain size controls on long-chain diol distributions and proxy signals in marine sediments

Abstract: Long chain alkyl diols (LCDs) are lipid biomarkers that occur ubiquitously in sediments. Their abundance and distributions are increasingly used as the basis of molecular proxies for environmental parameters such as sea surface temperature (SST) via the Long chain Diol Index (LDI), and upwelling intensity and nutrient conditions (parametrized as diol indices, DI-2, and Nutrient Diol Index, NDI, respectively). Their marine producers remain the subject of debate, but in cultures, they can be found within the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The SST‐SCA methodology has the potential to be extended to a global scale in the future, when a global database would be established based on the sediment grain‐size distribution in surface sediments and the SST values in different grain‐size sediments from the worldwide oceans. Moreover, the idea of the correction methodology would also be applied to other organic geochemical indicators that may also be potentially affected by hydrodynamics, such as long‐chain diols‐based upwelling and nutrient proxies (Lattaud et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The SST‐SCA methodology has the potential to be extended to a global scale in the future, when a global database would be established based on the sediment grain‐size distribution in surface sediments and the SST values in different grain‐size sediments from the worldwide oceans. Moreover, the idea of the correction methodology would also be applied to other organic geochemical indicators that may also be potentially affected by hydrodynamics, such as long‐chain diols‐based upwelling and nutrient proxies (Lattaud et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Additional source-specific biomarkers such as glycerol dialkyl glycerol tetraethers (GDGTs) (Damsté et al, 2002;Koga et al, 1993), long-chain alkyl diols (de Bar et al, 2020), and sterols (Tao et al, 2022) could further define the origin of organic matter, while other biomarkers such as algal-derived pigments, biopolymeric fraction of carbon, amino acids, and carbohydrates can determine its degree of reactivity (Burdige and Martens, 1988;Dauwe and Middelburg, 1998;Pusceddu et al, 2009;Raja and Rosell-Melé, 2022). Additionally, new proxies are continuously being proposed that can further disentangle the source of organic matter (Lattaud et al, 2021) and help refine the use of biomarker proxy calibration Tingley, 2014, 2018), which can be affected by sediment redistribution and degradation processes (Ausín et al, 2022;Lattaud et al, 2022). Future efforts will be directed into including these variables in MOSAIC to gain a holistic understanding of the fate of organic matter in marine sediments.…”
Section: Future Expansionsmentioning
confidence: 99%
“…surface ocean primary productivity, oxygen concentrations, sedimentation rates, etc.). This was first undertaken by Lee et al (2019) using a slightly expanded dataset of 5600 data points and was revisited by Atwood et al (2020) using 11 500 data points. While all of these studies agree that higher OC contents are found on continental margins in comparison to the open ocean, these margins are highly complex and temporally heterogenous, which is why more efforts should be directed towards compiling data in these areas.…”
Section: Introductionmentioning
confidence: 99%